Exploring Perceptions and Categorization of Virginia Hard Ciders through the Application of Sorting Tasks. (1st April 2021) - Kessinger, J'Nai; Earnhart, Grace; Hamilton, Leah; Phetxumphou, Katherine; Neill, Clinton; Stewart, Amanda C.; Lahne, Jacob
Abstract: Hard (alcoholic) ciders have grown rapidly since the early 2000s, but unlike beer and wine, there is limited scholarly research on their sensory attributes. The purpose of this study was to categorize and describe sensory and visual packaging and label attributes of ciders made in Virginia, United States using a labeled, free sorting task (a rapid sensory analysis method) with untrained panelists. In Study 1, N 1 = 49 panelists tasted and sorted K = 18 ciders into groups and labeled their groups. Then visually for Study 2, a second group of panelists ( N 2 = 61 ) sorted "photo sheets" of packaging and labels for the same K = 18 ciders by two separate tasks: According to how they expected the cider to taste; and What occasion they would be most inclined to consume the cider at . Classical text analysis was used to analyze descriptors from both the sensory and visual free sorting tasks, and the terms were projected onto their respective compromise similarity maps that were produced using DISTATIS. Subjects identified and described distinct sensory styles and attributes among the evaluated ciders; however, descriptions provided by producers on their labels did not align well with panelist experienced sensory attributes. Consistent sorting patterns from the photo sheets emerged—providing a first look into how ciders might be valued based on packaging and labels alone. The results of this research will help cider producers develop favorable products that will satisfy consumer expectations and encourage repeat purchase.